2017
DOI: 10.1002/adfm.201604981
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Generated Gold Nanoparticle Hybrid Polymersomes for Water‐Soluble Chemotherapeutics: Inhibited Leakage and pH‐Responsive Intracellular Release

Abstract: to liposomes, but with enhanced stability and more tunable functionalization. Since methoxy-poly(ethylene glycol)-b-polylactide vesicles were created, [5] polymersomes have played tremendously active roles as promising carriers for water-soluble drugs in the application of cancer therapy. Regarding drug release behavior, it is generally expected that polymersomes ought to hold as much cargo as possible in the circulatory system for a few hours or longer until they reach cancer tissue via enhanced permeability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…Gold nanoparticles were homogenously distributed among DEAB moieties and acted as inorganic cross‐links to aggregate polymeric chains ( Figure ). The results of the study indicated that not only did the drug accumulation in the tumor tissue increase in mice, but also that the pH‐responsive capability of the particles led to fast intracellular action while drug leakage at pH 7.4 was dramatically reduced …”
Section: Hybrid Vesicular Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold nanoparticles were homogenously distributed among DEAB moieties and acted as inorganic cross‐links to aggregate polymeric chains ( Figure ). The results of the study indicated that not only did the drug accumulation in the tumor tissue increase in mice, but also that the pH‐responsive capability of the particles led to fast intracellular action while drug leakage at pH 7.4 was dramatically reduced …”
Section: Hybrid Vesicular Delivery Systemsmentioning
confidence: 99%
“…Schematic image summarizing the method to incorporate gold nanoparticles into PNP nanoparticles and the intracellular release of the cargo due to the pH‐sensitive properties of the nanoparticle. Adapted with permission . Copyright 2017, Wiley.…”
Section: Hybrid Vesicular Delivery Systemsmentioning
confidence: 99%
“…Cavallaro and co‐workers prepared amphiphilic graft polymer containing amine and thiol groups for anchoring AuNPs to obtain a positive surface for siRNA delivery . Qiu and co‐workers prepared amphiphilic graft polymer with 2‐diethylaminoethyl 4‐aminobenzoate as hydrophobic pendant groups and PEG as hydrophilic chains for vesicle formation and high loading of DOX, as shown in Figure . AuNPs were in situ generated and homogeneously distributed in the polymer via coordination interaction as inorganic crosslinkers.…”
Section: Amphiphilic Polymers For Stabilizing Colloidal Aunpsmentioning
confidence: 99%
“…Amphiphilic graft polymer for loading anticancer drug to form the vesicles, which hybridize AuNPs via coordination interaction to prolong the systemic circulation time of the vesicles. Reproduced with permission . Copyright 2017, WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Amphiphilic Polymers For Stabilizing Colloidal Aunpsmentioning
confidence: 99%
See 1 more Smart Citation